Alien Mink Predation and Colonisation Processes of Rodent Prey on Small Islands of the Baltic Sea: Does Prey Naïveté Matter?. (13th May 2010) - Fey, Karen; Banks, Peter B.; Korpimäki, Erkki
Abstract : Colonisation, an important part of meta-population dynamics of fragmented populations, depends on both the dispersal ability and the ability to establish in the new habitat. Predation can hinder successful establishment of prey, and where the predation pressure comes from an alien predator, the effects on colonisation might be devastating. We studied the establishment of field voles ( Microtus agrestis ) inhabiting small islands of the archipelago of the Baltic Sea, SW Finland, under presence and absence of the alien American mink ( Mustela vison ). We translocated "experienced" voles from islands with mink, and "inexperienced" voles from islands from which mink had been removed, to other islands where mink was present or absent. By radio-tracking we studied survival, space and microhabitat use of voles within four weeks after translocation. Survival of voles on mink islands was significantly lower than on mink-free islands, but "experienced" voles did not survive better than "inexperienced" voles. "Experienced" voles were more often located in juniper habitats than "inexperienced" voles, but they appeared not to gain any survival benefit from altered microhabitat use. This study provides novel evidence, that alien mink predation inhibits establishment of colonising field voles and may thus ultimately induce extinction of voles from the outer archipelago.